Ethnolinguistic markers in translated texts of Tuvan folk-tales: a linguocultural commentary - Vorontsova, Galina N.; Gasanov, Mammadali M. (The New Research of Tuva, 2022)
The article presents the main principles of linguocultural commenting on the ethnolinguomarkers appearing in translated texts of Tuvan folk tales – all in all, 68 texts from five translated editions. The specific features of ethnically marked lexemes appear in both groups we have studied – proper and common nouns, each with respective sub-groups of their own. In translated texts these units can be dealt with by means of semantization, a lexical gap or finding a replacement. Ethnolinguomarkers which are proper nouns come as anthroponyms or place-names. Those which are common nouns can be further subdivided into those describing artefacts of material culture; plants and animals; words dealing with social structure; names of spirits and monsters; those dealing with Shamanist and Buddhists practices; and those marked “folklore word” in the dictionaries. Tuvan interjections preserved in Russian translations of folk tales belong to the class of untranslated ethnolinguomarkers. Besides this linguoculturological commentary that ethnically marked lexemes receive in the article, a purely cultural commentary is also important for understanding them. This kind of commentary provides information on folk customs, traditions and the mythological structure of the world.